# Solve for m (3m-2)/5=(4-m)/3

3m-25=4-m3
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(3m-2)⋅3=5⋅(4-m)
Solve the equation for m.
Simplify (3m-2)⋅3.
Apply the distributive property.
3m⋅3-2⋅3=5⋅(4-m)
Multiply.
Multiply 3 by 3.
9m-2⋅3=5⋅(4-m)
Multiply -2 by 3.
9m-6=5⋅(4-m)
9m-6=5⋅(4-m)
9m-6=5⋅(4-m)
Simplify 5⋅(4-m).
Apply the distributive property.
9m-6=5⋅4+5(-m)
Multiply.
Multiply 5 by 4.
9m-6=20+5(-m)
Multiply -1 by 5.
9m-6=20-5m
9m-6=20-5m
9m-6=20-5m
Move all terms containing m to the left side of the equation.
Add 5m to both sides of the equation.
9m-6+5m=20
14m-6=20
14m-6=20
Move all terms not containing m to the right side of the equation.
Add 6 to both sides of the equation.
14m=20+6
14m=26
14m=26
Divide each term by 14 and simplify.
Divide each term in 14m=26 by 14.
14m14=2614
Cancel the common factor of 14.
Cancel the common factor.
14m14=2614
Divide m by 1.
m=2614
m=2614
Cancel the common factor of 26 and 14.
Factor 2 out of 26.
m=2(13)14
Cancel the common factors.
Factor 2 out of 14.
m=2⋅132⋅7
Cancel the common factor.
m=2⋅132⋅7
Rewrite the expression.
m=137
m=137
m=137
m=137
m=137
The result can be shown in multiple forms.
Exact Form:
m=137
Decimal Form:
m=1.857142‾
Mixed Number Form:
m=167
Solve for m (3m-2)/5=(4-m)/3

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top